The Hajj and Europe in the Age of Empire (2016)
The present volume focuses on the political perceptions of the Hajj, its global religious appeal to Muslims, and the European struggle for influence and supremacy in the Muslim world in the age of pre-colonial and colonial empires. Readership: All interested in the connections of Europe with the Muslim world in the colonial age, and anyone interested in the transnational and global history of Europe and the Muslim world.